1996
DOI: 10.1097/00004032-199603000-00003
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Evaluating Bias and Uncertainty in Estimates of External Dose Obtained from Personal Dosimeters

Abstract: This paper describes an approach to quantifying errors in recorded estimates of external radiation dose obtained from personal dosimeters and applies the approach to dose estimates of workers at the Hanford site. Because a major objective of this evaluation is to provide the information needed for adjusting epidemiologic dose-response analyses of worker data for errors in dose estimates, the paper addresses the extent that errors for different workers are correlated, focuses on recorded doses as estimates of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Evaluations of the available annual external dosimetry data are important for interpretation of these studies, and for design of subsequent analyses (Cardis and Esteve, 1991) . Previous evaluations of the Hanford external dosimetry data have given attention to potential underestimated doses due to dosimetry techniques, the nature of exposure (e.g., the angle of exposure, the contribution of neutron, photon, Xray, and tritium doses ) , and recording practices at the facility ( Gilbert, 1990;Gilbert et al, 1996 ). Missing data, which are a more generic concern in occupational epidemiology studies, have been a subject of less discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations of the available annual external dosimetry data are important for interpretation of these studies, and for design of subsequent analyses (Cardis and Esteve, 1991) . Previous evaluations of the Hanford external dosimetry data have given attention to potential underestimated doses due to dosimetry techniques, the nature of exposure (e.g., the angle of exposure, the contribution of neutron, photon, Xray, and tritium doses ) , and recording practices at the facility ( Gilbert, 1990;Gilbert et al, 1996 ). Missing data, which are a more generic concern in occupational epidemiology studies, have been a subject of less discussion.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the degree of overestimation, we conducted a simulation study in which both actual doses and reported doses are known, so that the effect of censoring can be evaluated. Techniques proposed by Inskip et al (1987), Gilbert et al (1996), Mitchell et al (1997), and Xue and Shore (2003) for correcting censored measurements depend on knowledge about individual recorded doses. Since only annual cumulative doses are available for subjects in the NDR, such methods cannot be applied in our case.…”
Section: Censoring and The Ndr Datamentioning
confidence: 99%
“…In particular, the dosimeter measurement itself is a proxy for the internal exposure of relevant organs to ionizing radiation. A comprehensive discussion of bias and uncertainty associated with using personal dosimeters to estimate cumulative exposure to radiation can be found in Gilbert et al (1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations